A CFD-based simulation tool for the stability analysis of natural circulation systems. (November 2019) - Pini, A.; Cammi, A.; Lorenzi, S.; Cauzzi, M.T.; Luzzi, L.
Abstract: This paper presents a CFD-based simulation tool aimed at analysing the dynamics of natural circulation by means of the techniques provided by the linear stability theory. The tool can be adopted for a comprehensive stability analysis of free convection systems, giving information about the asymptotic behaviour, the spatial locations where perturbations have the largest impact on stability (i.e., a sensitivity analysis), and the so-called "transient energy growth", as well. The CFD-based approach overcomes the simplified hypotheses and the constitutive relations usually adopted to study the dynamic behaviour of natural circulation systems (i.e., one-dimensional approximation, correlations for pressure drops and heat transfer, …), and allows extending the analysis to complex geometries. The developed tool, that is based on a MATLAB ® -OpenFOAM ® coupling, has been assessed in a classic buoyancy-driven benchmark (i.e., the "differentially heated 2D cavity" test case), comparing the results with a classic Arnoldi-iteration approach and literature results. Subsequently, the study of the linear stability of a natural circulation loop facility has been performed, considering for the first time also the 3D representation of the system. The results have turned out to be satisfactory, being able to give proper information about the stability of natural circulation systems.